Seasonality effects over the ecological aquaculture of the native zooplanktivorous fish from South America Odontesthes bonariensis - García de Souza, Javier Ricardo (2017)
Ecological aquaculture systems consider the natural and social environments in which they are situated in the search to contribute to environmental sustainability. In South America, the aquaculture of the native zooplanktivorous fish Odontesthes bonariensis (“pejerrey”) has some constraints that could be overcome by applying extensive culture systems following an ecosystemic approach. This study represents the first attempt to develop ecological aquaculture in the region.An experiment of extensive cage culturewas carried out in La Salada de Monasterio Lake to answer how seasonal changes, both in physico-chemical and zooplankton features, affect the performance of pejerrey culture. Three successive rearing trials were carried out in spring, summer and autumn. The cageswere stockedwith pejerrey; whereas others (controls)were left without fish. Lake zooplankton abundance, biomass and species composition were different among seasons, with maximum abundance mean values during summer and maximum biomass mean values during spring. The zooplankton abundance found in cageswithout fish was higher than that registered in cages with fish, but no differences in species composition among those cages were detected. The pejerrey showed selective feeding habits throughout the entire experiment, and they fed mostly on copepods and cladocerans of N0.7 mm during spring and summer, especially after reaching 4 cm in total length, and on smaller copepods and cladocerans during autumn. The contribution of the different sizes of zooplankton to the gut contents was related to availability and to fish size, and the access to bigger zooplankton appeared to be a critical factor to promote better growth performance. The bigger fish were obtained in spring, when zooplankton biomass was maximum in the lake with greater representation of large cladocerans, with final fish weight eight times higher than that obtained in summer and fifty times greater than that obtained in autumn. The production obtained in spring was one and two orders of magnitude higher than that found in summer and autumn. The multiple linear regressions selected support the inference that seasonal temperature and zooplankton variations have effects on pejerrey growth in floating cages. Pampean lakes could be suitable environments to support pejerrey ecological aquaculture, and spring emerges as the better season to start an extensive culture that takes advantage of the zooplankton composition and dynamics. Statement of relevance to commercial aquaculture: Alternative tool to overcome constraints in pejerrey culture.